Expectations and experiences with physician care among patients receiving post-acute care in US skilled nursing facilities - Ryskina, Kira L. (BMC Geriatr, 2020)
BACKGROUND: In the US, post-acute care in skilled nursing facilities (SNFs) is common and outcomes vary greatly across facilities. Little is known about the expectations of patients and their caregivers about physician care during the hospital to SNF transition. Our objectives were to (1) describe the experiences and expectations of patients and their caregivers with SNF physicians in SNFs, and (2) identify patterns that differed between patients with vs. without cognitive impairment. METHODS: This qualitative study used grounded theory approach to analyze data collected from semi-structured interviews at five SNFs in January–August 2018. Patients admitted for short-term SNF care 5–10 days prior were eligible to participate. Thematic analysis was performed to detect recurrent themes with a focus on modifiable aspects of physician care. Analysis was stratified by patient cognitive impairment (measured by the Montreal Cognitive Assessment at the time of the interview). RESULTS: Fifty patients and six caregivers were interviewed. Major themes were: (1) patients had poor awareness of the physician in charge of their care; (2) they were dissatisfied with the frequency of interaction with the physician; and (3) participants valued the perception of receiving individualized care from the physician. Less cognitively impaired patients were more concerned about limited interactions with the physicians and were more likely to report attempts to seek out the physician. CONCLUSION: Patient and caregiver expectations of SNF physicians were not well aligned with their experiences. SNFs aiming to improve satisfaction with care may focus efforts in this area, such as facilitating frequent communication between physicians, patients and caregivers. SUPPLEMENTARY INFORMATION: Supplementary information accompanies this paper at 10.1186/s12877-020-01869-1.